Senso-Immunologic Prospects for Complex Regional Pain Syndrome Treatment - Okumo, Takayuki; Takayama, Yasunori; Maruyama, Kenta; Kato, Mami; Sunagawa, Masataka (Frontiers in Immunology, 2022)
A chronic pain syndrome, complex regional pain syndrome (CRPS), occurs in tissue injuries caused by surgery, trauma and ischemia. This severe painful condition has some clinical features such as redness and swelling of the affected skin. Intriguingly, it has been recently suggested that transient receptor potential ankyrin 1 (TRPA1) is involved in chronic post-ischemia pain (CPIP), a CRPS model. TRPA1 is a non-selective cation channel expressed in calcitonin gene-related peptides (CGRP)-positive primary nociceptor, and highly activated in ischemic condition followed by pain generation. In this review, we summarize the historical facts of TRPA1 and its involvement in pain sensation, inflammation and CRPS. Furthermore, it has been thought that bone atrophy is also a characteristic clinical sign of CRPS. The bone microstructure of CRPS patients could be altered by aggravated bone resorption via enhancement of osteoclast differentiation and activation. Although TRPA1 could be a target of pain treatment in CRPS, we also discuss about the paradoxical situation in this review. Nociceptor activation decreases the risk of bone destruction via CGRP secretion from the free nerve ending. Namely, TRPA1 inhibition could cause severe bone atrophy. However, the suitable therapeutic strategy is controversial because the pathological mechanisms of bone atrophy in CRPS have been unclear. Therefore, we would propose an importance to focus on the remission of abnormal bone turnover observed in CRPS through recently generated concept, senso-immunology.